2020
DOI: 10.1364/ol.383557
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal complexity of chaos in a phase-conjugate feedback laser system

Abstract: An 852 nm semiconductor laser is experimentally subjected to phase-conjugate time-delayed feedback achieved through four-wave mixing in a photorefractive (BaTiO 3 ) crystal. Permutation entropy (PE) is used to uncover distinctive temporal signatures corresponding to the sub-harmonics of the round-trip time and the relaxation oscillations. Complex spatiotemporal outputs with high PE mostly upwards of ∼0.85 and chaos bandwidth (BW) up to ∼31 GHz are observed over feedback strengths up to 7%. Low feedback region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 26 publications
1
15
0
Order By: Relevance
“…The latter is characterised by the self-pulsating dynamics regularly oscillating close to a multiple of the frequency of the external cavity [7,8]. Previously, we have also experimentally demonstrated that the PCF-generated chaos significantly enhances the chaos bandwidth when compared to the case of conventional optical feedback (COF) [9] and can exhibit highly spatiotemporally-complex outputs [10].…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…The latter is characterised by the self-pulsating dynamics regularly oscillating close to a multiple of the frequency of the external cavity [7,8]. Previously, we have also experimentally demonstrated that the PCF-generated chaos significantly enhances the chaos bandwidth when compared to the case of conventional optical feedback (COF) [9] and can exhibit highly spatiotemporally-complex outputs [10].…”
Section: Introductionmentioning
confidence: 94%
“…1 and is similar to the one in Refs. [7,10,19]. We use a commercial Fabry-Pérot laser diode emitting at 852 nm, model JDS-Uniphase SDL-5420.…”
Section: A Principle Of the Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…where the sliding mode surface s i is defined in (7). ε i , σ i , and c i are the positive constants.…”
Section: Observer-based Controller Design and Stability Analysismentioning
confidence: 99%
“…In the past decades, with the development of theoretical analysis methods of chaos, many chaos systems such as the Lorenz system [1], Rossler system [2], and Chen system [3] have been wildly studied. ese theoretical advancements of chaotic systems have been influentially applicated in many fields, such as power electrical systems [4,5], robotics [6], lasers [7], and secure communications [8]. Among these applications, to achieve the desired chaotic characteristic, the high-precision synchronization problem is the key problem that must be solved.…”
Section: Introductionmentioning
confidence: 99%